Social Media Utilization in Universitas Indonesia Library - Putri, Dinda Ayunindia (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2019)
This research discusses social media utilization activities held in the UI Library as a promotional tool. The purpose of this study is to describe social media use by UI Library. The research applies the qualitative approach and case study method. Informants were chosen by using a purposive sampling technique. Results show that UI Library has utilized social media in the form of Twitter and Instagram as a means to promote the collections, services, or even the facilities there. The library also used social media to collect users’ responses, either recommendations or complaints, which were taken as evaluation materials for service improvement. This study suggests that the library should make written policy or SOP (Standard Operating Procedure) about social media management as a media of promotions and increase the number of interactions with users on Instagram. Findings from this research may also be records in order to arrange an academic library’s social media application guide, particularly in Universitas Indonesia, and on a bigger scale, in Indonesia.